Primary Acinic Cell Carcinoma of the Breast: A Clinicopathological and Immunohistochemical Study - Kiyoshi Shingu; Tokiko Ito; Gengo Kaneko; Nobuo Itoh (Case Reports in Oncological Medicine)
Acinic cell carcinoma of the breast is an extremely rare, malignant neoplasm characterized by widespread acinar cell-like differentiation and clinically low-grade malignancy. Herein, we report a case of acinic cell carcinoma of the breast in a 41-year-old woman. The tumor was poorly demarcated but had a firm consistency. It was removed with lumpectomy, and sentinel lymph node biopsy was performed to check for metastasis. Microscopically, the tumor showed an infiltrative growth pattern with a combination of solid, trabecular, and microglandular areas. Many of the tumor cells had abundant clear vacuolated cytoplasm containing zymogen-typed granules which resemble acinar cells of the salivary glands. The immunohistochemical profile of the tumor was also similar to that of salivary gland acinic cell carcinoma: the tumor cells were positive for amylase, lysozyme, α-1-antichymotrypsin, S-100 protein, and epithelial membrane antigen and negative for estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2. She received postoperative chemoradiation therapy and has been well for 3 years since surgery. As studies on large series are lacking, further studies are needed to elucidate the biological characteristics of acinic cell carcinoma of the breast.